An analysis of the perceived societal benefits of and threats from trees for the delivery of livelihoods and community development - Tsvuura, S.; Mudhara, M.; Mabhaudhi, Tafadzwanashe (Wiley, 2023)
Societal Impact Statement: Understanding the perceptions of benefits and threats from trees is important for the livelihoods of communities. The study used focus group discussions, key informant interviews, and a questionnaire survey of 226 households in the province of KwaZulu-Natal, South Africa. The findings showed that household socio-economic factors such as gender and land tenure influenced perceptions of tree growing, and households that were involved in a tree restoration project viewed trees as contributing toward their livelihoods by reducing hunger. Hence there is a need to design strategies that promote socio-economic inclusivity of all households and genders and promote programs that increase awareness of ecosystem services within communities. Summary: Understanding the socio-economic factors that shape the way households value and utilize natural resources is critical in developing nature-based solutions. The study was aimed at understanding how the socio-economic circumstances of households determined their perceptions of the role of trees in livelihood delivery. A case study of Buffelsdraai and Osindisweni communities was used; these sites are adjacent to a municipal landfill where a tree restoration project intended to mitigate the effects of climate change is being implemented, and some of the households are involved in this project. The study used focus group discussions, key informant interviews, and a questionnaire survey of 226 households. It explored gender perspectives on the perceived benefits and threats of tree restoration. It analyzed the influence of households' economic characteristics and spatial configuration (the subdivisions of the landscape) to assess the impact of land tenure. The findings showed that gender influenced the perceptions that economic benefits can be derived from participating in the project. Households involved in the tree restoration project viewed trees as contributing to their livelihoods by reducing hunger. Households in peri-urban settlements, permanently resident in the area, showed greater reliance on natural resources than those in informal settlements and rural areas. Such differences can be attributed to differences in land tenure. Hence, there is a need to design strategies and operations that promote socio-economic inclusivity of all households and genders and reduce inequality. These findings are important for informing scaling to yield better climate change considerations and policies.